Minimizing energy consumption in a Job Shop problem with unidirectional transport constraint - Hadri, Abdelkader; Belkaid, Fayçal; Bougloula, Aimade-Eddine (13th International Colloquium of Logistics and Supply Chain Management (LOGISTIQUA), 2020)
In this work, we introduce the objective of minimizing energy consumption in a job shop scheduling problem with unidirectional transport constraint. In this problem, it is planned to process a set of N jobs (parts) on four machines. The Movement of jobs between these machines is in a single direction that is mean all the parts follow the same direction of movement. Indeed, the energy consumption in this type of problem depends; on the one hand on the speed of the machines processing the jobs and on the other hand on the speed of the means of transport. To solve this optimization problem, we have proposed a metaheuristic method that allows us to find a better sequencing of jobs in order to minimize the cost generated by energy consumption. Several simulations have been studied and the results obtained demonstrate the effectiveness of the proposed approach.